(Re)defining the euroregion concept - Medeiros, Eduardo (2011)
The INTERREG-A, the largest of the Community Initiatives, has been supporting the cross-border cooperation (CBC) in European Union (EU) territory, over the past 19 years, thus contributing to redraw a new political map of Europe, by reducing the barrier effect and reinforcing common development strategies. During this period, several new partnerships and institutions have been established, creating networks that connect a wider range of local and regional actors into the CBC process, on both sides of the borders. Some of these entities have gradually started to call themselves Euroregions, based on non-rigid criteria, even though, in some cases, they lack legal personality and operate on an informal basis. Moreover, it was recently approved by the European Commission the possibility to establish European Groupings of Territorial Cooperation, with legal personality, in border areas, to overcome the obstacles to the CBC process. Therefore, in this article, we propose a new CBC typology which looks at the concept of Euroregion in a geographical perspective, supported on different criteria and adapted to the present-day reality of the European border territories.